2018
DOI: 10.1371/journal.pntd.0006503
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of human and animal leptospirosis in the Pacific Islands reveals pathogen and reservoir diversity

Abstract: BackgroundThe Pacific Islands have environmental conditions highly favourable for transmission of leptospirosis, a neglected zoonosis with highest incidence in the tropics, and Oceania in particular. Recent reports confirm the emergence and outbreaks of leptospirosis in the Pacific Islands, but the epidemiology and drivers of transmission of human and animal leptospirosis are poorly documented, especially in the more isolated and less developed islands.Methodology/Principal findingsWe conducted a systematic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
84
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(94 citation statements)
references
References 92 publications
(109 reference statements)
8
84
0
2
Order By: Relevance
“…Leptospira serovars or serogroups usually demonstrate specific host preferences [6]. Our findings are in agreement with our current knowledge of host preferences: i.e.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Leptospira serovars or serogroups usually demonstrate specific host preferences [6]. Our findings are in agreement with our current knowledge of host preferences: i.e.…”
Section: Discussionsupporting
confidence: 92%
“…This study focuses on French Polynesia (FP) which is a French Overseas Country consisting of 22 territories in the South Pacific Ocean encompassing 118 atolls and islands [6]. Its overall population has been estimated to be 270,000 inhabitants.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic characterization showed that the ribosomal 16S gene sequence of E8 is identical to that of L. neocaledonica isolated from soil in New Caledonia and that it belongs to the intermediate clade (Figure ). However, low variability and the conserved nature of the ribosomal 16S gene sequences among the Leptospira species have previously been reported . DNA–DNA hybridization in silico revealed that E8 is a member of intermediate species and differs from L. neocaledonica .…”
Section: Discussionmentioning
confidence: 95%
“…Leptospirosis is one of the most widespread worldwide, and the number of cases is estimated at approximately 1.03 million annually (including 58,900 fatal cases) [3]. Primarily, leptospirosis outbreaks appear in regions with a tropical climate (such as the Pacific Islands region), where frequent floods and heavy rains contribute to the development of infection [4].…”
Section: Introductionmentioning
confidence: 99%